Glutamatergic pathways in the brains of turtles: A comparative perspective among reptiles, birds, and mammals - Hussan, Mohammad Tufazzal; Sakai, Akiko; Matsui, Hideaki (Frontiers in Neuroanatomy, 2022)
Glutamate acts as the main excitatory neurotransmitter in the brain and plays a vital role in physiological and pathological neuronal functions. In mammals, glutamate can cause detrimental excitotoxic effects under anoxic conditions. In contrast, Trachemys scripta, a freshwater turtle, is one of the most anoxia-tolerant animals, being able to survive up to months without oxygen. Therefore, turtles have been investigated to assess the molecular mechanisms of neuroprotective strategies used by them in anoxic conditions, such as maintaining low levels of glutamate, increasing adenosine and GABA, upregulating heat shock proteins, and downregulating KATP channels. These mechanisms of anoxia tolerance of the turtle brain may be applied to finding therapeutics for human glutamatergic neurological disorders such as brain injury or cerebral stroke due to ischemia. Despite the importance of glutamate as a neurotransmitter and of the turtle as an ideal research model, the glutamatergic circuits in the turtle brain remain less described whereas they have been well studied in mammalian and avian brains. In reptiles, particularly in the turtle brain, glutamatergic neurons have been identified by examining the expression of vesicular glutamate transporters (VGLUTs). In certain areas of the brain, some ionotropic glutamate receptors (GluRs) have been immunohistochemically studied, implying that there are glutamatergic target areas. Based on the expression patterns of these glutamate-related molecules and fiber connection data of the turtle brain that is available in the literature, many candidate glutamatergic circuits could be clarified, such as the olfactory circuit, hippocampal–septal pathway, corticostriatal pathway, visual pathway, auditory pathway, and granule cell–Purkinje cell pathway. This review summarizes the probable glutamatergic pathways and the distribution of glutamatergic neurons in the pallium of the turtle brain and compares them with those of avian and mammalian brains. The integrated knowledge of glutamatergic pathways serves as the fundamental basis for further functional studies in the turtle brain, which would provide insights on physiological and pathological mechanisms of glutamate regulation as well as neural circuits in different species.